Acute splenic sequestration and hypersplenism in the first five years in homozygous sickle cell disease. Issue 10 (October 1981) - Topley, J M; Rogers, D W; Stevens, M C; Serjeant, G R
Abstract : A cord blood screening programme initiated in June 1973 had screened 68 000 normal deliveries by February 1979 with the detection of 216 cases of homozygous sickle cell disease. Regular review of these children in the Medical Research Council paediatric clinic has identified acute splenic sequestration as a major cause of morbidity and mortality in the first 5 years of life. In addition to classical episodes characterised by peripheral circulatory failure, minor episodes of increasing anaemia associated with an enlarging spleen and an active marrow were also common. These minor episodes appeared to have predictive value in children who later developed severe life-threatening episodes of acute splenic sequestration. Sequestration. Sustained hypersplenism was also appreciably more common in children developing minor or major episodes of acute splenic sequestration compared with those without such a history. It is proposed that the classification of acute splenic sequestration be expanded to include these minor episodes, and that consideration be given to prevention of recurrences by splenectomy particularly in patients who also develop sustained hypersplenism.